2021
DOI: 10.1155/2021/5578568
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Interleukin-23 Levels in Patients with Oral and Cutaneous Lichen Planus

Abstract: Lichen planus is considered a chronic inflammatory disease which affects different sites, such as the skin, mucous membranes, hair, and nails. Based on the evidence, a complex cytokine network plays a crucial role in lichen planus pathogenesis. The study was aimed at assessing the serum IL-23 levels in the patients with cutaneous and oral lichen planus compared to healthy controls. Method. The study included 30 cutaneous lichen planus patients, 20 oral lichen planus patients, and 33 control subjects. Five mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Later observations noted a response of IL-12/23 inhibition on one patient with LP pemphigoides ( 195 ), and three patients with LP ( 96 , 196 ). Use of IL-12/23 was grounded on the observation of increased IL-23 expression in oral LP ( 84 ), as well as an increased serum concentration of IL-23 in LP patients ( 197 ). Of note, we are not aware of any study addressing the impact of IL-12/23 inhibition in LP.…”
Section: Managementmentioning
confidence: 99%
“…Later observations noted a response of IL-12/23 inhibition on one patient with LP pemphigoides ( 195 ), and three patients with LP ( 96 , 196 ). Use of IL-12/23 was grounded on the observation of increased IL-23 expression in oral LP ( 84 ), as well as an increased serum concentration of IL-23 in LP patients ( 197 ). Of note, we are not aware of any study addressing the impact of IL-12/23 inhibition in LP.…”
Section: Managementmentioning
confidence: 99%
“…22,23 Interestingly, IL-23 has been reported to be expressed in human OSCC cell lines and OSCC tissues to promote OSCC growth. 24,25 Therefore, IL-23, either macrophages-derived or OSCC-derived, might influence the function of OSCC-infiltrating Tregs if they express IL-23R. However, to our knowledge, this has not been reported by previous studies.…”
Section: Introductionmentioning
confidence: 62%
“…Recent research also demonstrated the significance of IL‐23R in the differentiation and function of Th1 and Th2 cells 22,23 . Interestingly, IL‐23 has been reported to be expressed in human OSCC cell lines and OSCC tissues to promote OSCC growth 24,25 . Therefore, IL‐23, either macrophages‐derived or OSCC‐derived, might influence the function of OSCC‐infiltrating Tregs if they express IL‐23R.…”
Section: Introductionmentioning
confidence: 99%
“…29 Additionally, an overexpression of IL-23, one of the hallmarks of Tregs, has been found up-regulated in serum of OLP individuals, suggesting that this signature molecule probably participates in the induction of Th17 differentiation in OLP. 56 In fact, a positive correlation has been found between IL-17 and IL-23 at both protein and mRNA levels, 22,31 indicating that the upregulation of IL-17 might be associated with the overexpression of IL-23 in early stages of OLP. 22 Another contributing factor in the lack of differentiation of Th17 towards Th1 cells may be the oral flora as it can exert a direct influence on the host immunity by altering the T-cell functional activity.…”
Section: Discussionmentioning
confidence: 99%